Performance analysis of a novel method for fast handovers in TDD and FDD for long term evolution - K.Venkatesh, G; V.Rao, P (International Journal of Engineering and Technology, 2018)
The LTE Long Term Evolution highly developed Technology, Handover is the essential function of the mobility of user in cellular networks in Time Division Duplex as well as Frequency Division Duplex. Handover is one of the essential that can affect the [QoS] Quality of Service with Capacity of Mobile Broadband Networks. Within mobile cellular network communication systems, a (spectrum) limited shared resource needs to be shared with all the users, so full duplex communication is achieved. This paper involves studying diverse Hand over delay parameters and also focus on reducing â€œHard Handover delayâ€ by minimizing interruption time, activation time, wireless channel accesses time as well as the wireless link transmission delay. Technique is developed in order to reduce the handover delay time in Time Division Duplex network which too reduces the wireless channel access time and the wireless link transmission delay. A novel handover algorithm is developed which would decreases the handover delay time and access time inside mobile network environment.Additional work may be conceded on to obtain enhanced performance and Quality of service in Time Division Duplex mobile network.